Determinants of Survival and Mortality Patterns in 99 Consecutive Burn Admissions at a North-Indian Tertiary Network: A Retrospective Cohort Study - Dr Anubhav Goel; Dr. Prakhar singh; Dr. Shivam khandelwal; Dr Nikhil, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background. Burns remain a major cause of injury in low- and middle-income countries, yet granular outcome data from North-Indian districts are scarce. Methods. We retrospectively analysed 99 consecutive acute thermal-injury admissions (January 2023 – March 2024) to four linked tertiary units in western Uttar Pradesh. Demographic, clinical-burn and outcome variables were extracted from prospectively maintained ward registers and validated against referral slips. Primary outcome was in-hospital survival; secondary outcomes were timing and proximate cause of death. Categorical data were compared with χ² or Fisher’s exact test and continuous variables with t- or Mann–Whitney-U tests; p<0.05 was significant. Results. Mean age was 32 ± 15 years (range 10 months–75 years); 57 patients were male (57.6%). Median total body surface area (TBSA) burned was 38 % (IQR 22–60 %). Overall survival was 38 % (38/99). Survival exceeded 80 % for TBSA < 20 % but fell sharply to 14 % for 60–80 % TBSA and nil for > 80 % (Table 2, Figure 2). Of 61 deaths, 26 (42.6 %) occurred within 72 h (early deaths), predominantly from airway obstruction with inhalational injury, whereas 35 (57.4 %) were delayed, chiefly due to septic and/or hypovolaemic complications (Table 3). Increasing TBSA, third-degree depth, and inhalation injury were independent predictors of mortality on multivariable analysis (all p<0.01). Conclusion. In this under-resourced regional network, survival remains unacceptably low once TBSA exceeds 40 %, and deaths shift from airway-related to septic aetiology after 72 h. Extending critical-care capacity and infection-control bundles beyond the first week is likely to yield the greatest mortality benefit.